Movin’ on up? A survey experiment on mobility enhancing policies - Barton, Jared; Pan, Xiaofei (European Journal of Political Economy, 2022)
We use a nationwide survey experiment in the United States to measure whether information on intergenerational economic mobility or policy-specific arguments influence support for six pro-mobility policies advocated by political entrepreneurs. We find the information treatments do not affect support, but the argument treatments significantly increase support for three of the policies. We also include a behavioral measure by allowing respondents the opportunity to write their U.S. Senators. We find argument treatments significantly increase the likelihood that letters address economic mobility and significantly promote advocacy for that policy in the letter, but no increase in advocacy from the information treatments. Our results persist after controlling for a variety of robustness measures.